VASODILATOR EFFECT OF OCTYLMETHOXYCINNAMATE ON HUMAN UMBILICAL ARTERIES - Verde, Ignacio; Filipe, Juliana (Health and Society, 2021)
Octylmethoxycinnamate (OMC) is a filter for ultraviolet B radiation used in sunscreens to protect skin. There is some evidence about the OMC activity as endocrine disruptor concerning a possible estrogenic activity, but its vascular effects were not still analyzed. The objective was to evaluate the non-genomic effects of the OMC on human umbilical artery (HUA) without endothelium. By mean of an organ bath system, HUA rings without endothelium were contracted by 5-hydroxytryptamine (5HT; 1µM) or by depolarization with KCl (60mM), and the effect of different concentrations of OMC was analyzed. The OMC elicits vasodilator effect on HUA without endothelium contracted by 5-HT (1μM) and by KCl (60mM). The effect was similar for the two contractile agents used. Here, we established that the OMC causes vasodilation of human arteries. This effect is analogous to the non-genomic effect caused by estradiol (E2), which occurs also by and endothelial-independent mechanism.